Energy Efficiency Processing of Three Layer Reinforced Concrete Exterior Wall Panels - Aknaz Анар (Рroblems of engineering and professional education, 2023)
Today, widespread construction of houses with a monolithic frame, but during the construction of these houses used to perform labor-intensive processes walling using small-piece items that significantly increase the cost of construction. Therefore there is a need for industrial bearing, self-supporting or curtain walling. The introduction of new regulations on energy saving and the rising cost of fuel and energy resources have given new impetus to the construction industry to the development and application of energy-efficient building envelopes. Some of these energy-efficient building envelopes, in which both are combined carrying and heat-shielding properties are three-layer protecting concrete panels with an average effective thermal insulation layer with a flexible coupling.